A multi-strain probiotic promoted recovery of puppies from gastroenteritis in a randomized, double-blind, placebo-controlled study - Molina, Rosa A. (2023)
Objective and animals. Acute diarrhea is among the most common causes of veterinary consultations for dogs. A double-blind, placebocontrolled intervention trial was done with 120 puppies with gastroenteritis. These dogs were 1 to 4 mo old, male and female, of various breeds and sizes. Procedure. Dogs were randomly allocated into 2 groups: Those in the treated group (TG) received a multi-strain probiotic with Lactobacillus johnsonii CRL1693, Ligilactobacillus murinus CRL1695, Limosilactobacillus mucosae CRL1696, and Ligilactobacillus salivarius CRL1702 (1 3 109 CFU/mL) daily for 7 d, whereas those in the control group (CG) received a placebo. All puppies received intravenous fluids, an antiparasitic, amoxicillin PO, and enrofloxacin SC. Results. At the start of the trial, the 2 groups were similar. Probiotic administration for 7 d normalized fecal consistency, with 69, 50, and 80% of small, medium, and large puppies in the TG achieving a fecal score of 1 (separate hard lumps) at 7 d, significantly better than puppies in the CG. After 7 d of treatment, most puppies (70%) in the TG had an excellent recovery, whereas in the CG, recoveries were 35.7% “bad” and 30.4% “fair.” Therefore, treatment with probiotics hastened recovery (P , 0.0001). At the end of the trial, there was a significant increase of cultivable lactobacilli in the feces of TG puppies, but no significant differences between the 2 groups in numbers of total mesophylls, enterobacteria, or Gram-positive cocci. Total mortality was 5.8%, including 4 puppies from the CG and 3 from the TG. Conclusion. In a randomized, double-blind, placebo-controlled study, puppies with gastroenteritis symptoms receiving a multi-strain probiotic had rapid improvement, implying beneficial effects on the microbiota and its functionality.